The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3847/2041-8213/acadd7
|View full text |Cite
|
Sign up to set email alerts
|

PHANGS–JWST First Results: Variations in PAH Fraction as a Function of ISM Phase and Metallicity

Abstract: We present maps tracing the fraction of dust in the form of polycyclic aromatic hydrocarbons (PAHs) in IC 5332, NGC 628, NGC 1365, and NGC 7496 from JWST/MIRI observations. We trace the PAH fraction by combining the F770W (7.7 μm) and F1130W (11.3 μm) filters to track ionized and neutral PAH emission, respectively, and comparing the PAH emission to F2100W, which traces small, hot dust grains. We find the average R PAH = (F770W + F1130W)/F2100W values of 3.3, 4.7, 5.1, and 3.6 in IC 5332, NGC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 87 publications
4
28
0
Order By: Relevance
“…We find that all 12 show strong PAH emission at 3.3 μm and fall in a region of the F335M versus F330M − F335M CMD that clearly separates from the vast majority of detections. To first order, the PAH emission at 3.3 μm appears to correlate with other dust emission (Sandstrom et al 2023a(Sandstrom et al , 2023bDale et al 2023;Chastenet et al 2023aChastenet et al , 2023b and so should represent a sensitive, high-resolution tracer of dust-reprocessed UV light from young stars. Based on this, we develop criteria to select a larger sample of candidates.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We find that all 12 show strong PAH emission at 3.3 μm and fall in a region of the F335M versus F330M − F335M CMD that clearly separates from the vast majority of detections. To first order, the PAH emission at 3.3 μm appears to correlate with other dust emission (Sandstrom et al 2023a(Sandstrom et al , 2023bDale et al 2023;Chastenet et al 2023aChastenet et al , 2023b and so should represent a sensitive, high-resolution tracer of dust-reprocessed UV light from young stars. Based on this, we develop criteria to select a larger sample of candidates.…”
Section: Discussionmentioning
confidence: 98%
“…In Figure 2, we show color-magnitude diagrams (CMDs) based on F335M and F300M photometry; the former captures flux from the PAH 3.3 μm feature, while the latter primarily probes the stellar and dust continuum (Lee et al 2023;Sandstrom et al 2023aSandstrom et al , 2023bChastenet et al 2023aChastenet et al , 2023b. Panel (a) in Figure 2 shows the 12 visually identified prototype embedded clusters (yellow stars) together with the sample of F335M sources detected using Photutils find_peaks (black dots).…”
Section: Selection Criteria For Embedded Cluster Candidatesmentioning
confidence: 99%
“…The measurements underpinning this model must be highly resolved because radiation field, density, and ISM phase can vary by factors of ∼1000 on 10-100 pc scales, altering the PAHs (Chastenet et al 2019;Draine et al 2021). The PHANGS-JWST first results in this Issue from Chastenet et al (2023aChastenet et al ( , 2023b, Dale et al (2023), andEgorov et al (2023) all show that PAH emission properties do indeed vary systematically with the local galactic environment.…”
Section: Characterizing How Dust Properties Respond To the Local Envi...mentioning
confidence: 98%
“…Using empirical methods, Sandstrom et al (2023a) demonstrated how to isolate PAH features from the stellar continuum using JWST bands, which can be developed into a full set of PAH-only maps of the galaxies. Chastenet et al (2023aChastenet et al ( , 2023b used JWST data to find variation in PAH properties in the broader ISM, with Egorov et al (2023) and Dale et al (2023) exploring H II regions and star clusters, respectively. These ratio measurements can be refined into environmental diagnostics of properties like the metallicity and radiation field.…”
Section: Data Productsmentioning
confidence: 99%
“…Specifically, the wavelength coverage of the Mid-Infrared Instrument (MIRI) is perfectly suited to this task, as it is sensitive to several polycyclic aromatic hydrocarbon (PAH) emission features (e.g., at 7.7 μm; see Draine & Li 2007;Smith et al 2007;Li 2020). Emission from PAHs is particularly useful in tracing the shells of feedback-driven bubbles (e.g., Pineda et al 2022), due to (a) the increased gas densities found in swept-up shells (PAHs are generally well mixed with the gas and illuminated by the average interstellar radiation field such that they trace the gas column very sensitively; e.g., Regan et al 2006;Leroy et al 2013;Chown et al 2021;Gao et al 2022;Leroy et al 2023), (b) the high number of ionizing photons emitted by the OB association powering the bubbles, leading to PAHs being destroyed in the photoionized interiors of the bubbles (e.g., Galliano et al 2018;Chastenet et al 2023aChastenet et al , 2023bEgorov et al 2023), and (c) the low optical depth from the shell interior to the edge, which will allow far-UV photons to easily heat the small dust grains (e.g., Draine & Li 2007;Draine 2011;Hensley & Draine 2021). Together, these cause the edges of bubbles to appear with high contrast against their interior PAH emission (e.g., Churchwell et al 2006;Watson et al 2008).…”
Section: Introductionmentioning
confidence: 99%